2017
DOI: 10.1016/j.artint.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Constrained clustering by constraint programming

Abstract: Constrained Clustering allows to make the clustering task more accurate by integrating user constraints, which can be instance-level or cluster-level constraints. Few works consider the integration of different kinds of constraints, they are usually based on declarative frameworks and they are often exact methods, which either enumerate all the solutions satisfying the user constraints, or find a global optimum when an optimization criterion is specified. In a previous work, we have proposed a model for Constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 33 publications
(55 reference statements)
0
37
0
Order By: Relevance
“…This framework enables the modeling of different constrained clustering problems, by specifying an optimisation criterion and by setting the user constraints. The framework is evolved by improving the model and by developing dedicated propagation algorithms for each optimisation criterion (Dao et al, 2017). In this model, the number of clusters K does not need to be fixed beforehand, only bounds are needed K min ≤ K ≤ K max and the model has three components: partition constraints, user constraints, and objective function constraints.…”
Section: Constraint Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…This framework enables the modeling of different constrained clustering problems, by specifying an optimisation criterion and by setting the user constraints. The framework is evolved by improving the model and by developing dedicated propagation algorithms for each optimisation criterion (Dao et al, 2017). In this model, the number of clusters K does not need to be fixed beforehand, only bounds are needed K min ≤ K ≤ K max and the model has three components: partition constraints, user constraints, and objective function constraints.…”
Section: Constraint Programmingmentioning
confidence: 99%
“…This problem aims to find clusters that are both compact (minimising the maximal diameter) and well separated (maximising the split), under user constraints. In (Dao et al, 2017) it is shown that to solve this problem, the framework can be used by iteratively changing the objective function and adding constraints on the other objective value. This framework has been extended to integrate user constraints on properties, in order to make clustering actionable .…”
Section: Constraint Programmingmentioning
confidence: 99%
“…The first one uses constraint to enhance machine learning techniques with declarative constraints, e.g. in solving constrained clustering problems and in data mining techniques that handle domain specific constraints [19,20,21]. One recent example is the work of Ganji et al [20] who proposed a logical model for constrained community detection.…”
Section: Related Workmentioning
confidence: 99%
“…Later, Chabert et al have introduced two new CP models for computing optimal conceptual clusterings. The first model (denoted FullCP2) may be seen as an improvement of [6]. The second model (denoted HybridCP) follows the two step approach of [17] : the first step is exactly the same; the second step uses CP to select formal concepts.…”
Section: Related Workmentioning
confidence: 99%
“…Distance-based clustering aims at finding homogeneous clusters only based on a dissimilarity measure between objects. Different declarative frameworks have been developed, which rely on CP [6] or ILP [1,15]. There are a few existing approaches for obtaining balanced clusters.…”
Section: Related Workmentioning
confidence: 99%